Endovascular Management of Middle Aortic Syndrome Presenting with Uncontrolled Hypertension - Owen S. Glotzer; Kathryn Bowser; F. Todd Harad; Sandra Weiss (Case Reports in Vascular Medicine)
Middle Aortic Syndrome is a rare vascular disorder consisting of narrowing or stenosis of the distal thoracic or abdominal aorta. It is described in the literature in the form of case studies and case series. The authors present an unusual case of Middle Aortic Syndrome attributed to Takayasu’s arteritis in a 60-year-old female who presented to the emergency department with uncontrolled hypertension. Traditional intervention involves open surgical bypass. This case study reviews the published literature on this rare syndrome and illustrates a successful alternative to open surgery through an endovascular approach.